Boron-containing organic pigments from a Jurassic red alga - Wolkenstein, Klaus; Gross, Jürgen H.; Falk, Heinz (Proceedings of the National Academy of Sciences of the United States of America, 2010)
Organic biomolecules that have retained their basic chemical structures over geological periods (molecular fossils) occur in a wide range of geological samples and provide valuable paleobiological, paleoenvironmental, and geochemical information not attainable from other sources. In rare cases, such compounds are even preserved with their specific functional groups and still occur within the organisms that produced them, providing direct information on the biochemical inventory of extinct organisms and their possible evolutionary relationships. Here we report the discovery of an exceptional group of boron-containing compounds, the borolithochromes, causing the distinct pink coloration of well-preserved specimens of the Jurassic red alga Solenopora jurassica. The borolithochromes are characterized as complicated spiroborates (boric acid esters) with two phenolic moieties as boron ligands, representing a unique class of fossil organic pigments. The chiroptical properties of the pigments unequivocally demonstrate a biogenic origin, at least of their ligands. However, although the borolithochromes originated from a fossil red alga, no analogy with hitherto known present-day red algal pigments was found. The occurrence of the borolithochromes or their possible diagenetic products in the fossil record may provide additional information on the classification and phylogeny of fossil calcareous algae.